Evaluasi Konsep Missio Dei dalam Pemikiran Lesslie Newbigin - Harianja, Doni Herwanto (Sekolah Tinggi Teologi Intheos Surakarta, 2024)
Abstract. This article aimed to review the concept of missio Dei in the thought of Lesslie Newbigin, as well as to examine the criticisms and evaluations directed towards him. At first glance, Newbigin's concept of missio Dei emphasizes centrifugal movement rather than to centripetal movement within the church. In this regard, utilizing the missio Dei framework proposed by Stefan Paas, the author conducted a reexamination of Newbigin's thought and evaluates the criticisms directed towards it. This study demonstrated that in Newbigin's conceptualization, which tends to emphasize centrifugal aspects, also contains centripetal aspects within it.Abstrak. Artikel ini bertujuan untuk mengulas kembali konsep missio Dei dalam pemikiran Lesslie Newbigin, serta meninjau kritikan maupun evaluasi yang ditujukan kepadanya. Sekilas dalam konsep missio Dei Newbigin sangat menekankan gerakan sentrifugal dibandingkankan gerakan sentripetal di dalam gereja. Dalam hal ini, dengan menggunakan kerangka pemikiran missio Dei dari Stefan Paas, penulis melakukan penyelidikan kembali terhadap pemikiran Newbigin, dan mengevaluasi kritikan yang ditujukan kepadanya. Penelitian ini menunjukkan bahwa konsep pemikiran Newbigin yang cenderung menekankan aspek sentrifugal, di dalamnya juga terkandung aspek sentripetal.